COVID-19 -An Insight into Various Impacts on Health, Society and Economy - Venkatachary, Sampath Kumar; Prasad, Jagdish; Samikannu, Ravi; Baptist, Leo John; Alagappan, Annamalai; Ravi, Rohini (International Journal of Economics and Financial Issues, 2020)
The declaration of COVID 19 as pandemic has impacted the society at large. In what started with 17 cases in Wuhan spread its tentacles and has now over 4 million cases across the globe. In this rapidly changing environment, it is extremely difficult to quantify the impacts that the virus has on many aspects of society. The paper highlights the various challenges and the impact on society, economy and general health. These are only initial levels impacts, and it goes on with greater implications on growth depends on many factors, including the social distancing norms and shutdown rules laid by countries. Nonetheless, it is clear that the virus is here to stay and is likely to impact growth, health and society substantially. Keywords: Covid-19, Health, Economy, Society JEL Classifications: E, I1 DOI: https://doi.org/10.32479/ijefi.9925